2022
DOI: 10.1111/bjdp.12416
|View full text |Cite
|
Sign up to set email alerts
|

Infant behavioural effects of smartphone interrupted parent‐infant interaction

Abstract: Infants are vulnerable to changes in the dyadic synchrony with their caregivers, as demonstrated in numerous experiments employing the still‐face paradigm. The sudden lack of attunement causes infant stress reactions and the still‐face literature have suggested potential long‐term costs of this in terms of development of social, emotional and cognitive skills. Acknowledging the rapid technological development accompanied by altered practices in the parent‐infant interaction, the current study investigates infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 50 publications
(66 reference statements)
0
14
0
Order By: Relevance
“…Ventura et al 15 described a negative impact of electronic devices during breastfeeding in some aspects of interaction in the short term, such as the responsiveness to the mother's encompassed actions. Similarly, Tidemann and Melinder 16 suggested a negative impact of smartphone use on the relationship between infants and parents, reporting a reduction in infant engagement and an increase in protest behaviour such as crying and kicking. Conversely, Inoue et al 17 did not find any negative impact of smartphone use on bonding.…”
Section: Discussionmentioning
confidence: 98%
“…Ventura et al 15 described a negative impact of electronic devices during breastfeeding in some aspects of interaction in the short term, such as the responsiveness to the mother's encompassed actions. Similarly, Tidemann and Melinder 16 suggested a negative impact of smartphone use on the relationship between infants and parents, reporting a reduction in infant engagement and an increase in protest behaviour such as crying and kicking. Conversely, Inoue et al 17 did not find any negative impact of smartphone use on bonding.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with adults' negative responses to smartphone use during in-person interactions, several studies claimed that children tend to display negative emotions when they observe adults using smartphones [64][65][66]80]. Modified still-face studies have shown that infants respond with increased negative affect when the parents pretend to use a smartphone [64][65][66].…”
Section: Smartphone Use In Face-to-face Adult-child Interactionsmentioning
confidence: 89%
“…Lack of access to the content that the phone-user focuses on is thought to affect the partner's response [62] and making the content of the smartphone a shared focus between the partners is considered a good strategy to remedy negative emotional impacts [58,63]. Withholding eyecontact and contingent acknowledgements and responses is thought to be a typical part of phone use during in-person interactions [30,53,61,[64][65][66] and it is thought responsible for reflexive activation of feelings of being excluded and ostracized [30,40,53]. Notably, both eyecontact and contingent turn-taking are key behavioral signals regulating attribution of ostension and expectations related to them are indeed bound to be frustrated when the communication partner engages with a smartphone.…”
Section: Smartphone Use In Face-to-face Social Interactionsmentioning
confidence: 99%
“…These observational findings are consistent with experimental studies that illustrate parents are less sensitive to their children’s cues, engage less frequently with their children, and exhibit less warmth and affection, resulting in overall lower quality parent–child interactions when technological distractors are present compared to when they are not (Krapf-Bar et al, 2022; Lederer et al, 2022; Ochoa et al, 2021; Ventura et al, 2019). Infants and young children notice when their parents become distracted by mobile devices during parent–child interactions, and exhibit increases in negative affect, distress, and disengagement and decreases in positive affect in response (Myruski et al, 2018; Stockdale et al, 2020; Tidemann & Melinder, 2022). In sum, parents’ device use, especially when heavy and absorbing, is associated with lower parenting effectiveness, poorer sensitivity and responsiveness to children’s behavioral cues and needs across many contexts, and lower quality interactions with children.…”
Section: The Current Studymentioning
confidence: 99%